Central cholinergic and adrenergic mechanisms in the release of antidiuretic hormone - Bhargava, K. P. (1972)
1. Studies on the urine outflow, blood ADH concentration and electrolyte excretion were carried out in α-chloralose anaesthetized hydrated dogs; the agonists and antagonists of specific cholinoceptors and adrenoceptors were injected by the intracerebroventricular technique, to delineate the role of the C.N.S. receptors in the control of ADH secretion. 2. Central injection of acetylcholine elicited a dose-dependent antidiuretic response which was associated with an increase in the blood ADH titre. Central atropinization partially blocked the antidiuretic response. The remaining antidiuretic response was reversed to a diuretic one by further pretreatment with phenoxybenzamine. The diuretic response thus obtained could be blocked by propranolol. 3. The α-adrenoceptor agonists, phenylephrine and noradrenaline, induced dose-dependent antidiuretic responses with a concomitant rise in blood ADH concentration. Their effect could be blocked by pretreatment centrally with phenoxybenzamine. Low doses of adrenaline induced a diuretic response and a decrease in blood ADH concentration, higher doses elicited a dose-dependent antidiuretic response and increase in the titre of ADH in blood. Central phenoxybenzamine pretreatment reversed the antidiuretic effect of high doses of adrenaline to a diuretic effect which could be blocked by propranolol. 4. Isoprenaline elicited a dose-dependent diuretic response and a decrease in blood ADH titre and propranolol competitively blocked the effect of isoprenaline. 5. It is concluded that central muscarinic cholinoceptors and the α-adrenoceptors are concerned in the release of ADH, whereas the β-adrenoceptors are concerned with inhibition of ADH release.